DOLIQUIDITY CONSTRAINTS INFLUENCE THE TECHNICAL EFFICIENCY OF WHEAT GROWERS? EVIDENCE FROM PUNJAB, PAKISTAN - Y. Mehmood; K. Rong1; M. Arshad; M. K. Bashir (Journal of Animal and Plant Sciences, 2017)
This article examined the influence of liquidity constraints on technical efficiency of wheat growers in Punjab province of Pakistan. We designed a theoretical model that identifies the possible reasons of liquidity constraints embodied by credit quantity rationing, transaction cost rationing and households risk reluctance behaviour. Primary data was collected from 518 wheat growers from five districts of Punjab. Based on direct elicitation method we categorized wheat growers into liquidity constrained wheat growers (LCWG) and liquidity unconstrained wheat growers (LUWG). We then, employed stochastic frontier analysis (SFA) approach to estimate the technical efficiency of wheat growers. The results indicate that mean technical efficiency difference between LCWG and LUWG was 9 percent. In the second stage of analysis,our inefficiency effects model disclosed that, technical efficiency of both groups of growers were influenced byeducation level, family size, sowing time, access to extension services, off-farm income and savings of the household head. In addition, credit size had significant positive effect, while interest rates on principal amount had significant negative effect on technical efficiency of both groups of growers.
Keywords: asymmetric information; risk rationing; non-price rationing; SFA; wheat; Pakistan